2017
DOI: 10.1038/s41598-017-01154-z
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of crystal structures in GeTe during phase transition

Abstract: We investigated changes in the crystal structure of GeTe during its phase transition. Using density functional theory (DFT) calculations, four possible crystal structures were identified: R3m, P1, Cm, and Fm3m. Among these, P1 and Cm were examined here for the first time. By calculating the internal energy of the crystal volume change, we verified that P1, R3m, and Cm can coexist in crystalline GeTe. The X-ray diffraction spectra of annealed and laser-irradiated GeTe films revealed coexisting P1 or R3m and Cm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 32 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…Many experimental studies show two modes around 90 and 120 cm −1 or two modes around 120 and 140 cm −1 or even three modes around 90, 120 and 140 cm −1 . The mode at about 140 cm −1 is often identified as an intrinsic GeTe mode [3,[28][29][30]. In Fig.1, by comparing a freshly cleaved surface to a surface exposed to ambient conditions we show that this mode is due to surface oxidation and also obtained if a freshly cleaved surface is washed with ethanol.…”
mentioning
confidence: 71%
“…Many experimental studies show two modes around 90 and 120 cm −1 or two modes around 120 and 140 cm −1 or even three modes around 90, 120 and 140 cm −1 . The mode at about 140 cm −1 is often identified as an intrinsic GeTe mode [3,[28][29][30]. In Fig.1, by comparing a freshly cleaved surface to a surface exposed to ambient conditions we show that this mode is due to surface oxidation and also obtained if a freshly cleaved surface is washed with ethanol.…”
mentioning
confidence: 71%
“…Finally, we will discuss the Raman spectrum of h‐GaTe that is still controversy in previous works. Previous work found that after long time exposure in ambient environment, the Raman pattern of m‐GaTe will turn very close to Raman pattern of h‐GaTe, therefore, the main peak of ≈ 127 and 143 cm −1 are attributed to chemisorption of oxygen to Te . However, some works based on calculation and experiment insist on the two peaks belonging to intrinsic Raman peaks of h‐GaTe .…”
Section: Resultsmentioning
confidence: 99%
“…The low-temperature phase of GeTe is a rhombohedral structure with lattice parameters of a = 4.156 Å and c = 10.663 Å and the space group of R3m. [103] On increasing the temperature over 700 K, GeTe undergoes a phase transition [104][105][106][107][108] and adopts a cubic structure with a lattice parameter of a = 5.996 Å and the space group of Fm ̅ m. [109] Figure 2a,b show the crystal structures of R-GeTe and C-GeTe, respectively. In C-GeTe, Ge is octahedrally bonded with six Te atoms, whereas in R-GeTe, Ge is bonded with three closer and three further Te atoms.…”
Section: Crystal Structures and Chemical Bondingmentioning
confidence: 99%